Disaster Preparedness and Staff Well-being in Healthcare Staff: A Comprehensive Study in the UAE - Alsuwaidi, Mahra (Global Journal of Health Sciences, 2023)
Purpose: This paper examines the crucial role of healthcare administrators in the United Arab Emirates (UAE) in ensuring both disaster preparedness and staff well-being. Methodology: It uses mixed methods to review the literature on emergency medical teams in disaster response and the prevalence and impact of burnout among healthcare workers. It also explores factors and interventions to prevent and reduce burnout in the UAE context. Findings: Key findings are that administrators have a vital role in preparedness and need strategies for service continuity and quality. They also need to address staff burnout and its impact on patient care by implementing interventions to prevent and reduce it. Unique Contribution to Theory, Practice and Policy: The paper proposes recommendations for healthcare administrators in the UAE to improve their disaster preparedness and staff well-being strategies based on evidence and best practices. Disaster preparedness and staff well-being are interrelated in healthcare administration, affecting patient care quality and safety. Administrators should integrate well-being initiatives into preparedness planning and leverage related resources and expertise. Recommendations for healthcare organizations include enhancing preparedness efforts, prioritizing staff well-being, and integrating related interventions for positive implications on staff and patient health and well-being, organizational resilience and performance, and community resilience. The paper emphasizes administrators' important roles in promoting preparedness and staff well-being in the UAE context.